A study on scrape smear cytology in oral leukoplakia in a tertiary health care centre of southern Assam - Ullah, Sania S.; Deka, Manoj K.; Khakhlari, Nitumani (International Journal of Research in Medical Sciences, 2020)
Background: Oral cavity is susceptible to countless changes with advancing, environmental, and lifestyle related habits and factors. Oral mucosal lesions especially related to chewing and smoking of tobacco have led to the increased incidence and prevalence of potentially malignant and malignant disorders worldwide. Oral leukoplakia has been a very frequent finding in patients coming to our department and with an increasing rise of oral squamous cell carcinoma in the region, the study was conducted. Methods: Patients referred to our section from various department with white oral lesion. Scrapping smears were prepared. Stained with MGG and PAP stain. Study period: January 2019 to May 2020. Results: Total number of patients with white oral lesion were 83. Out of these 65 were male and 18 were female. Most of the patients had addiction to betel nut and leaf with tobacco and few had history of intake of bidi for several years. Conclusions: The study reveals that most of the oral leukoplakia cases is attributed to smoking, betel nut and lime intake. Exfoliative cytology of oral mucosa serves to be an easy, convenient and reproducible technique for early diagnosis of premalignant condition. Biopsy can be used as an adjunct in cases showing atypia and mixed type of keratosis.